Demystifying the Saintly Image of Gandhi: A Rhetorical Reading of Orwell’s “Reflections on Gandhi” - Pandey, Hem Lal; Upadhyay, Toya Nath (The Outlook: Journal of English Studies, 2024)
This paper analyses George Orwell’s essay “Reflections on Gandhi” to explore how Orwell dwells on Gandhi’s contradictory character traits between his saintly ideals and the pragmatic needs of humanism. This paper argues that Orwell intends to justify Gandhi as a humanist politician by demystifying the saintly image crafted through his physical attributes, autobiographical narratives, and the mainstream political discourse. To discuss this issue, the present study has made a rhetorical reading of the text and relies on the method of textual analysis. The findings of the study suggest that Orwell strategically employs persuasive techniques, including timely arguments, authentic portrayal of positions, evidence-based logical reasoning, and stylistic patterns to convey his perspective of humanist Gandhi effectively. Finally, this paper contributes to have a deeper understanding of his critique of Gandhi's persona and the broader implications to the political discourse such as Gandhism.